Impact of Patriarchal Norms on Economic Security of Women in North Central Nigeria - Aliegba, Becky Ade; Adadu , Yahaya; Alhaji, Usman Yusuf (Kashere Journal of Politics and International Relations, 2025)
This study examines the impact of patriarchal norms on the economic security of women in North Central Nigeria. The main objective is to analyze the different theoretical perspectives and findings of studies conducted by various scholars to ascertain the impact of patriarchal norms on women's economic security in North Central Nigeria. This study employs a thematic literature review and analysis of existing research reports from reputable sources to identify the key findings and recommendations related to the impact of patriarchal norms on women's economic security in North Central Nigeria. The study finds out that patriarchal norms in North Central Nigeria reinforce traditional gender roles that limit women's access to education, employment opportunities, and economic resources. Also, that women in North Central Nigeria face systemic barriers to inheritance rights, and access to financial credit systems due to discriminatory cultural practices. Based on the findings, the study suggested that the federal and state ministries of women affairs in collaboration with civil societies should push for legal reforms to eliminate discriminatory practices and ensure gender equality in land ownership, inheritance laws, and access to financial services traditional gender roles and stereotypes, and promote policies and programmes that encourage women's participation in diverse economic sectors. Relevant non-governmental organisations should undertake legal reforms to eliminate discriminatory practices and ensure gender equality in inheritance laws, and access to financial services, complemented by public awareness campaigns and capacity-building initiatives to educate women about their rights.